Process, Types and Applications of 3D Printing Technologies - Krishna Reddy, Vaka Vamshi; Sreenivasarao, Devavarapu; Khasim Saheb, Shaik (International Journal of Computer Sciences and Engineering, 2025)
“Improvement usually means doing something that we have never done before”, says Shigeo Shingo, world’s leading expert on manufacturing practices. This principle has been followed, consciously or unconsciously, in almost every industry for the development of the self and the society. The manufacturing industry is one of the fastest growing industries ensuing from this doctrine. With the advancements in Science and Technology, better techniques and efficient methods are being developed to minimize the outright efforts for manufacturing a product. Before the coinage of 3D printing(3DP) technologies, one has to depend on classical plots which are less efficient and time-consuming. But now, the implications of 3D printing technologies have changed the fate of the manufacturing industry. Over and above Manufacturing, 3DP has a profound influence on other industries such as Aerospace industry, Consumer goods industry, Medical industry, Education and so on. This paper elaborates various steps and processes involved in manufacturing a product using 3DP, types of 3DP and their boundless applications in various sectors.